Legal Settlement of Cases of Misuse of Personal Data in Prepaid Cellular Card Registration - Djasman, Shandy; Puluhulawa, Fenty U.; Meiske Kamba, Sri Nanang (Universitas Negeri Gorontalo, 2024)
The purpose of this research is to find out the legal settlement process for cases of misuse of personal data in prepaid cellular card registration. Researchers use the type of empirical juridical research is to use the type of field research (field research). By using a descriptive study, a systematic, factual and accurate description or painting of the facts, nature and relationship between the phenomena being investigated. The result of this research is that there are indications of the practice of utilizing customer personal data for the personal interests of unscrupulous outlet officers. Some cases show that customer data, such as phone numbers and addresses, are misused for the purpose of offering other products or services that are not related to cellular card registration. This clearly violates the principle of personal data protection and harms consumer trust. The practice of selling customers' personal data to third parties without the knowledge and consent of the data owner was revealed. Some mobile card registration outlets are known to sell customer data, such as demographic profiles and call history, to marketing companies or other service providers for commercial purposes. This practice not only violates privacy rights, but can also lead to potential misuse of data by irresponsible parties. There have been cases of falsification of customers' personal data by unscrupulous outlet staff for certain purposes. Some reports stated that the outlet staff recorded false or incomplete data in the registration form, hindering the process of identity verification and monitoring by the mobile operator. This practice not only violates the law, but can also trigger various criminal acts, such as identity theft.